2002
DOI: 10.1159/000048253
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the MSC Cold Cap System in the Prevention of Chemotherapy-Induced Alopecia

Abstract: Objective: To study the effectiveness of the MSC cold cap system to prevent chemotherapy-induced alopecia. Methods: The system was applied in 83 cancer patients (mean age 49.8 years) undergoing chemotherapy with alopecia-causing agents. Seven patients did not tolerate the system. Seventy-six patients were evaluable for assessment; 26 received anthracycline (group A), 33 taxane (group T), 5 anthracycline plus taxane (group AT), 7 intravenous etoposide (group E) and 5 ifosfamide with or without other alopecia-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…The manufacturers of these devices were unable to satisfy the FDA's request and, ultimately, these systems failed due to lack of data. However, newer scalp cooling methods that provide more uniform and controlled cooling are undergoing evaluation in Europe with substantial benefit reported against a number of chemotherapy regimens [7,24,40,42].…”
Section: Current and Future Therapeutic Modalitiesmentioning
confidence: 99%
“…The manufacturers of these devices were unable to satisfy the FDA's request and, ultimately, these systems failed due to lack of data. However, newer scalp cooling methods that provide more uniform and controlled cooling are undergoing evaluation in Europe with substantial benefit reported against a number of chemotherapy regimens [7,24,40,42].…”
Section: Current and Future Therapeutic Modalitiesmentioning
confidence: 99%
“…Although such treatments were found to be successful in reducing alopecia in connection with certain chemotherapy regimens, they were difficult to standardize and not generally useful over the wide range of pharmacological regimens used in the clinic. Although more recent studies utilizing improved hypothermia devices reported increased reliability, certain antineoplastic drug combinations, notably combinations comprising a taxane could not be protected against (Katsimbri et al 2000;Christodoulou et al 2002). Among the many pharmacological approaches for alopecia prevention that were investigated, vitamin D 3 appeared to be the most promising protective compound because it was effective against several different antineoplastic agents in preclinical experiments (e.g., Jimenez et al 1995;Schilli et al 1998).…”
mentioning
confidence: 99%
“…There are no approved preventative treatments for CIA in humans although several experimental and pharmacological approaches are under evaluation. Treatments to prevent or minimize alopecia include physical means such as scalp tourniquets (no longer used due to patient discomfort) 20 and scalp hypothermia, 11,21 and pharmacologic means that include topical vitamin D 3 analogue, 22 AS101, 23 Minoxidil [24][25][26] or Cs 27,28 and other experimental drugs. 19 Most of these treatments have either limited or very selective activity or have not been tested in humans yet.…”
Section: Discussionmentioning
confidence: 99%